Environmental education towards the Great Green Macaw (Ara ambiguus) reintroduction project in Ecuador - Montenegro-Pazmiño, Eliana Carolina (2020)
Species reintroductions are long-term processes that involve various ecological and social factors. The success of these types of projects depends largely on the relationships between all the stakeholders involved: NGO’s, authorities, local communities, among others. Environmental education is a key tool to create links between public or private organizations, and the local communities. In this paper, we present a study case of the environmental education process around the Great Green Macaw reintroduction project in the Ayampe community reserve, Manabí province, Ecuador. The objectives of the environmental education activities are related to the long-term conservation of the Great Green Macaw and to empower the communities and local stakeholders towards a better quality of life based in more responsible attitudes towards the natural environment. We analyze this process from its scope, perspectives, goals, themes and spaces.